PENGARUH DISIPLIN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI KELAS XII IPS SMA NEGERI 2 MUARO JAMBI - RTS. Miftahul Jannah; Diliza Afrila (Universitas Batanghari Jambi, 2023)
This study aims to find out the effect of discipline and learning motivation on learning outcomes in economics class XII IPS SMA Negeri 2 Muaro Jambi. This research is a quantitative study, the total population of this study were 123 students and the number of samples was 95 students. With a significant level of 5%. Selection of this sample using Proportional Random Sampling Technique. Data collected using questionnaires or questionnaires and documentation. The method used is descriptive analysis and multiple regression analysis. The results showed from the test of the coefficient of determination, it can be seen from the R Square table of 0.708, which means that learning outcomes are influenced by learning discipline and learning motivation by 0.708 or 70.8% while the remaining 29.2% is influenced by other variables not examined in this study. Based on table 4.13 above, it is known that the sig value is 0.024 <0.05 and it can also be seen that the calculated F value of 3.906 is greater than the F table value of 3.09. Then H0 is rejected and Ha is accepted, which means that learning discipline and learning motivation simultaneously have a significant effect on learning outcomes. Keywords : Discipline, Learning Motivation, Learning Outcomes